A Modified Semi-Analytic Iterative Method for Solving a Class of Partial Integro-Differential Equations with Conformable Fractional Order Derivative - Salim, Ahmed; H. Mohammed, Osama (Al-Nahrain Journal of Science, 2020)
In this paper, we introduce a modified semi analytic iterative method for solving conformable fractional Partial Integro-Differential equations (CFPIDEs). The methodology is tested by some illustrative examples which are given to demonstrate its accuracy, applicability and efficiency.